DAMPAK INSIDEN KANSO 1944 TERHADAP KOMUNITAS TIONGHOA DI PARIAMAN SUMATERA BARAT - Fitri, Refligy Yulia; Ibrahim, Bedriati; Melay, Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : Indonesia is a country that has a large diversity of tribes, one of which is the Minangkabau tribe who inhabit the western part of Sumatra. One of the areas in West Sumatra, Pariaman, has been visited by ethnic Chinese, due to its geographical condition and natural wealth. Initially the ethnic Chinese relationship with the Pariaman people was very peaceful, but after the arrival of Japan a harmonious life between the Pariaman people and the ethnic Chinese became chaotic. At this time the Pariaman area can no longer be found by ethnic Chinese. the factor of ethnic Chinese departure from Pariaman was one of them because of the Kanso incident in 1944. This was very interesting to study, where good relations between Pariaman people and Chinese ethnicity turned into an inharmonious relationship, to sharpen the research the research objectives were formulated in terms of how Chinese entered to Pariaman, how was the life of the Chinese community before the Kanso incident, how were the social relations between the Pariaman and Chinese people before the incident, how the incident occurred and the impact of the incident on the Chinese. The method used is a qualitative method. The results of this study indicate that it turned out that the chance incident occurred as a result of ethnic Chinese actions which caused anger to Pariaman people such as giving daughters to Japanese soldiers, committing immorality near places of worship and the biggest anger of the Pariaman people when one ethnic Chinese leaked all the actions along with the place the hideout of Pariaman fighters to Japan. As a result of the acts of violence which led to the killing of many ethnic Chinese, they were afraid to be in Pariaman. After this incident many of the ethnic Chinese were reluctant to return to Pariaman. In addition to the sense of trauma, the Pariaman region itself is now an administrative area.Key Words: Kanso 1944 incident, Pariaman, Chinese ethnic